Effect Of Competitive Collective Method According To Variable Training To Develop Layup Shooting Accuracy In Basketball For Students - Ramy Jabbar Kazem Abboud (Gelora : Jurnal Pendidikan Olahraga dan Kesehatan IKIP Mataram, 2026)
The current research aims to investigate effect of a collective competition method based on variable training in developing accuracy of layup shooting in basketball among fourth-year students. researcher used experimental method with an equivalent groups design to suit nature of problem and study’s objectives. study was conducted on a purposive sample of fourth-year students at College of Physical Education and Sports Sciences, University of Babylon, for academic year 2024-2025, numbering 36 student. To collect data, the researcher used standardized skill tests to measure accuracy of aiming. After ensuring homogeneity and equivalence of sample in terms of dependent variables, participants were equally divided into two groups an experimental group and a control group. Statistical results yielded that variable exercise applied in group competition style achieved remarkable progress and proved more effective in developing accuracy of layup shooting compared to traditional method used with control group, there are statistically significant differences between pre-test and post-test, in favor of post-test for experimental group. In light of these findings, researcher recommends that need to adopt a group competition approach supported by variable training as a basic strategy in basketball skills training and learning programs. Importance of diversifying learning and training methods and not being satisfied with traditional pattern, to ensure that learners’ motivation is stimulated and their skills and precise abilities are developed.